Mechanical compliance of the endocardium - Bin Choy, Young; Cao, Hong; Tungjitkusolmun, Supan; Tsai, Jang Zern; Haemmerich, Dieter; Vorperian, Vicken R.; Webster, John G. (My University, 2002)
Radio-frequency (RF) ablation is an accepted treatment for cardiac arrhythmias related to abnormal focal cardiac substrate. The penetration depth of the electrode into the endocardium affects lesion size, a critical determinant of success of RF ablation. We measured the relation between the mechanical compliance and the penetration depth of RF ablation catheter electrode at frequently ablated areas of the endocardium and examined the influence of time after death on mechanical properties of the tissue. We measured force versus time for eight insertion depths of the catheter electrode into full-thickness endocardial samples derived from the mitral valve annulus, the left ventricular free wall and the tricuspid valve annulus. We varied the time after death at 15, 40min, 3, 8, and 18h and repeated our measurements. At 15min after death, the first 0.5mm penetration depth caused the fastest relaxation at 55s. Force decay decreased dramatically at 15min after death as the penetration depth increased from 0.5 to 4mm. We used the force data sampled at 60s after insertion to approximate the elasticity. We observed the relations between the force versus the insertion depth. The force increased by a factor of 5 for the mitral valve annulus and 8 for the left free wall from 15min to 18h. We derived coefficients of a second-order polynomial equation relating the force data to insertion depth with R2>0.99. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Elastic component; Insertion depth; Relaxation effect; RF ablation